2011
DOI: 10.1177/1440783311407945
|View full text |Cite
|
Sign up to set email alerts
|

The Professionalization of Children’s Services in Australia

Abstract: This article examines the concept and practice of the 'professionalization' of children's services in Australia, emphasizing the importance of gender, skills and regulation. Children's services practitioners have difficulty in reaching professional status -broadly defined. Tertiary-level training and credentials alone are insufficient as the expertise of the work in centre-based services is not 'socially sanctioned'. The coexistence of family day care diminishes the status of centrebased workers. To achieve pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…The likelihood of wage equity being successfully addressed through market mechanisms seems remote however, as the costs and wage implications of better-paid educators are often seen as antithetical to the interests of employers and/or families (Woodrow 2007;Lyons 2011). Recent Productivity Commission reports (2011, 2014), for example, have recorded the reluctance of educators to ask for higher wages, and of employers to offer them, because increased costs would be most likely passed on to families in the form of higher fees, potentially leading to the removal of some children from services.…”
Section: An Appropriately Remunerated Workforce?mentioning
confidence: 99%
See 1 more Smart Citation
“…The likelihood of wage equity being successfully addressed through market mechanisms seems remote however, as the costs and wage implications of better-paid educators are often seen as antithetical to the interests of employers and/or families (Woodrow 2007;Lyons 2011). Recent Productivity Commission reports (2011, 2014), for example, have recorded the reluctance of educators to ask for higher wages, and of employers to offer them, because increased costs would be most likely passed on to families in the form of higher fees, potentially leading to the removal of some children from services.…”
Section: An Appropriately Remunerated Workforce?mentioning
confidence: 99%
“…Seen in this way, educators' rights to fair pay, and children's and families' interests, need not be seen as mutually exclusive. It could also be argued that if calls for improved public recognition of professional status are not matched by improved remuneration, the undervaluation of educators' practice might be perpetuated (Lyons 2011).…”
Section: An Appropriately Remunerated Workforce?mentioning
confidence: 99%
“…As quality assurance standards seeks to homogenise the evaluation of service quality in centre-based and family day care, the possible ways of describing family day care service quality are reduced. Given the already marginalised position of family day care within early years discourse (Lyons, 2012), it is likely that the particularities of family day care, such as childhood freedom, an authentic home environment and connection with community (Hand, 2005) may be lost. Detached, observable, measurable service quality overrides the quality of human experience.…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, motivation and pride for the profession would be fostered (Institute of Medicine and National Research Council, 1992). For example, Lyons (2012) examined the concept and practice of "professionalization" of children's services in Australia, and found that gender, skills and regulation played an important role. As long as the society does not recognise the expertise, there will be real challenges to reaching professional status even if the workforce had the relevant credentials.…”
Section: Resultsmentioning
confidence: 99%